Targeting platelet-derived growth factor receptor β inhibits the proliferation and motility of human pterygial fibroblasts. (2nd September 2019) - Mai, Weiqian; Chen, Minfeng; Huang, Maohua; Zhong, Jincheng; Chen, Jian; Liu, Xiaoyong; Deng, Juan; Yang, Xiaoxi; Ye, Wencai; Zhang, Rijia; Zhou, Qing; Zhang, Dongmei
ABSTRACT: Background : Pterygium, a common eye disease with high postoperative recurrence, lacks effective therapeutic strategies. Therefore, it's urgent to identify specific targets to develop rationally targeted molecular drugs for the pterygial therapy. Methods : The cell proliferation and motility were studied in both the primary human pterygial fibroblasts (hPFs) and an ex vivo pterygium model. hPFs transfected with the pCMV3- PDGFRB plasmid, PDGFRB siRNA and CRISPR/Cas9 system were used to determine the role of PDGFR-β in pterygial fibroblasts functions. Western blotting, immunohistochemistry and immunofluorescence were performed to evaluate the expression of the key proteins. Results : PDGFR-β expression in the pterygial stroma and primary hPFs was significantly higher than that in the conjunctiva and human conjunctival fibroblasts. PDGF-BB promoted the proliferation, migration and invasion of hPFs, which can be significantly suppressed by sunitinib via inhibition of the PDGFR-β/extracellular signal-regulated kinase (ERK) pathway. In the ex vivo model, the knockout of PDGFRB and sunitinib treatment blocked the proliferation and motility of fibroblasts in the pterygial stroma via the suppression of PDGFR-β/ERK pathway. Conclusion : This study demonstrates that PDGFR-β may be a potential therapeutic target for pterygium, and inhibition of PDGFR-β by sunitinib is a promising and effective approach for pterygium treatment.